FAKTOR - FAKTOR YANG MEMPENGARUHI KEPUTUSAN INVESTASI PADA INVESTOR SAHAM DI SURABAYA - ANENDY PUTRI, RAMADHANI; ISBANAH, YUYUN (Jurnal Ilmu Manajemen (JIM), 2019)
The number of investors in Indonesia from June 2017 to June 2018 has an impact on investment activities. Investment activities related to investment decision making by investors are influenced by various factors. The factors discussed in this study are Herding, Risk Perception, Risk Averse, Financial Literacy, and Demographic Factors towards Investment Decisions. This study uses a sample of 220 stock investors registered at the Investment Gallery in Surabaya, and uses multiple linear regression analysis techniques through SPSS 23. The results show that the herding variable influences investment decisions, while risk perception, risk averse, financial literacy, and demographic factors including gender, age, income, education, and experience have no effect on investment decisions. The implication of the results of this study is to provide knowledge about aspects and factors that influence investment decision making. Keywords: demographic factors; financial literacy; herding; risk averse; risk perception.